Learning Civic Education Based on Local Culture of North Sulawesi Society - Theodorus Pangalila; Juliana Margareta Sumilat; Kosmas Sobon (Journal of International Conference Proceedings, 2021)
Indonesia is currently experiencing significant problems related to its national character. The issue of federal character leads to further weakening of the younger generation's understanding of the noble values of Pancasila, which are sourced from the Indonesian local wisdom. This is because the local wisdom values of the community are less discussed by the teacher, let alone associated with the learning material being taught. Teachers in delivering learning materials are more focused on explicitly stated material in the learning curriculum. This study aims to identify the local wisdom of North Sulawesi values that can be used in Civics gaining knowledge of the elementary, junior excessive, and excessive college levels. This study is a qualitative study with records series thru observation, interviews, and literature have a look. Sources of records on this have a look at have been students, teachers, and principals. This has a look at that the values of neighborhood awareness of North Sulawesi are still less internalized in the Civic Education learning process; therefore, this study recommends developing an education model based on the North Sulawesi local cultures.